Does excessive alcohol consumption contribute to the development of anxiety disorder? - Pikulicka, Agata; Świercz, Kamila; Kulbat, Mateusz; Majcher, Monika; Kulbat, Aleksandra; Górska, Dominika; Majcher, Magdalena; Sierpień, Małgorzata; Karwańska, Aleksandra; Brzychczy, Piotr (Journal of Education, Health and Sport, 2023)
Introduction Over past decades the number of patients suffering from psychiatric disorders all around the world is constantly increasing. Thank to general awareness and less stigmatization people seek for specialist’s help more willingly. Recently, one of the most common diagnoses has been anxiety disorder and many of them also tend to abuse alcohol. So far, scientists have focused mostly on alcoholism as a consequence of anxiety disorder, due to patients’ predilection to addictions. However, ethanol can also trigger anxiety itself. Aim of the study The aim of this study is to summarize the current state of knowledge on the role of alcohol in anxiety disorder development and its pathomechanisms. Material and methods This article is based on available publications in Pubmed and Google Scholar databases. Conclusions Excessive alcohol consumption may lead to the development of anxiety disorder in some patients, as well as, many other psychiatric disturbances. However, further research must be done to find out precise pathomechanism responsible for those states.